Low Tariffs for Energy Resources and Real Interest of Beneficiaries - Karyan, Ara (Journal of Sociology: Bulletin of Yerevan University, 2017)
The article discloses the importance of goal-setting of greening (or ecologization) of the tax system for the Republic of Armenia, presented it theoretical and methodological basis, objectives and approaches of its application in international practice. It presents a comparative evaluation of core differences between reduction of tariffs for natural gas and electricity to consumers through the differentiated tariffs and introduction on the same source of energies excise tax and justified advantages of the introduction of the excise tax on natural gas and electricity for immediate beneficiaries and all other participants of the process
Keywords: environmental taxes, concept of